Three-Dimensional Silk Fibroin/Chitosan Based Microscaffold for Anticancer Drug Screening - Niu, Hui; Xiao, Jiarui; Lou, Xiaoli; Guo, Lingling; Zhang, Yongsheng; Yang, Runhuai; Yang, Hao; Wang, Shouli; Niu, Fuzhou (Frontiers in Bioengineering and Biotechnology, 2022)
Traditional monolayer cell cultures often fail to accurately predict the anticancer activity of drug candidates, as they do not recapitulate the natural microenvironment. Recently, three-dimensional (3D) culture systems have been increasingly applied to cancer research and drug screening. Materials with good biocompatibility are crucial to create a 3D tumor microenvironment involved in such systems. In this study, natural silk fibroin (SF) and chitosan (CS) were selected as the raw materials to fabricate 3D microscaffolds; Besides, sodium tripolyphosphate (TPP), and 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC) were used as cross-linking agents. The physicochemical properties of obtained scaffolds were characterized with kinds of testing methods, including emission scanning electron microscopy, x-ray photoelectron spectroscopy, fourier transform infrared spectroscopy, water absorption, and swelling ratio analysis. Cancer cell lines (LoVo and MDA-MB-231) were then seeded on scaffolds for biocompatibility examination and drug sensitivity tests. SEM results showed that EDC cross-linked scaffolds had smaller and more uniform pores with great interconnection than the TPP cross-linked scaffolds, and the EDC cross-linked scaffold exhibited a water absorption ratio around 1000% and a swelling ratio of about 72%. These spatial structures and physical properties could provide more adhesion sites and sufficient nutrients for cell growth. Moreover, both LoVo and MDA-MB-231 cells cultured on the EDC cross-linked scaffold exhibited good adhesion and spreading. CCK8 results showed that increased chemotherapeutic drug sensitivity was observed in 3D culture compared with 2D culture, particularly in the condition of low drug dose (<1 μM). The proposed SF/CS microscaffold can provide a promising in vitro platform for the efficacy prediction and sensitivity screening of anticancer drugs.